The Effects of Combined Micron-Scale Surface and Different Nanoscale Features on Cell Response - Yi Kang; Xuelei Ren; Xin Yuan; Li Ma; Youneng Xie; Zeyu Bian; Jun Zuo; Xiyang Wang; Zhiming Yu; Kechao Zhou; Qiuping Wei (Advances in Materials Science and Engineering)
Sandblasting and acid-etching (SLA) and anodization are the two most commonly used methods for surface modification of biomedical titanium. However, there are unavoidable problems such as residual sand particles and lack of hydrophilicity on the surface of titanium sheets treated with SLA technology. In addition, titanium implants showed only the micro/submicroscopic structure. In order to avoid the residue of sand particles in the surface of titanium, the two surface treatments etching treatment (E) and etched-anodizing (EA) on titanium were used, and their surface topography, surface chemistry, and surface roughness were compared with those of the SLA control group. Their wettability and the biocompatibility were also compared and evaluated. The results show that both E and EA samples have the micro/nano hierarchical structure and better wettability compared with the SLA samples. Their performances, especially the E surfaces, were enhanced in terms of cell adhesion, spreading, proliferation, and differentiation abilities.